STUDI TERHADAP RENCANA PELAKSANAAN PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SMP NEGERI BANJARMASIN - Sarbaini, Sarbaini (Vidya Karya Jurnal Kependidikan, 2015)
The basic value of democration are the obedience to norms of law and orderliness, which is also become the characteristic of a democratic citizhen. The character could be thought through the civics education based on the character of obedience of student at school, especially to student at secondary level (SMP). For some schools at secondary level in Banjarmasin, there are students who have the obedience to the norm of orderliness with high, medium, and low category. The purpose of this study is to explore the lesson plan of civics education for organizing the model of building obedience character to the norms of orderliness as the effort in preparing democratic citizen at school. This study used a qualitative method. The technic used in collecting data is documentation study. The data was analyzed by a qualitative analysis. The result of this study is that the lesson plan of civics education still not based on affective domain and also not integrating the obedience character yet.